HOMEOSTASIS OF UNCOMPLICATED PREGNANCY IN THIRD TRIMESTER - OKSANA N. Novikova; GALINA A. Ushakova; LILIYA R. Mustafina; SERGEY V. Logvinov (Фундаментальная и клиническая медицина)
Aim. To investigate the homeostasis of uncomplicated pregnancy in the third trimester.Materials and Methods. We recruited 136 consecutive pregnant women. at 37-41 weeks of gestation. Other criteria of inclusion were normal vaginal microbiota during the pregnancy and absence of placental inflammation. Exclusion criteria were past medical history of obstetric or gynecological complications, vaginal dysbiosis, addictions (smoking, drug addiction, alcoholism), and placental inflammation.Results. In the third trimester, both mother and fetus frequently showed the normal adaptation, adequate reactions to the load tests, recovery capabilities, and sufficient heart rhythm variability. In addition, we found a strong correlation between maternal and fetal heart rhythm variability. Conclusions. Maternal and fetal heart rhythm variability can be considered as a marker of the homeostasis during the third trimester.